STUDENTS’ SPEAKING SKILL THROUGH ANIMATION MOVIE - Pipit Rahayu (Universitas Putera Batam, 2015)
This Paper discusses about the analysis of Students Speaking Skill through animation movie. Animation movie is included in audiovisual media. In addition, animation movie is kind of film which involve sound, recording a series of draing of manipulating in animate object, one frame is one time. The technique of data analysis is descriptive qualitative. The steps involved analyzing the component of speaking skill (accent, fluency, vocabulary, grammar and comprehension). Besides, the students had to watch the animation movie that they have chosen before. After that in the group of work they had to discuss the story then present it in oral presentation in front of the class. The Sample in this paper was the second semester students which consist of 40 students. Based on the analysis, it can be concluded that students’ speaking skill through animation movie was in good category. It can be seen from the summary of data, 79,5% of students was in good category in comprehension, 67,5% of students was in good category on fluency, 75% of students was good category in vocabulary, 59% of students was in good category in term of grammar and 79,75% of students was in good category in term of accent.